Novel NAD-independent D-lactate dehydrogenases from Acetobacter aceti and Acidocella species MX-AZ02 as potential candidates for in vitro biocatalytic pyruvate production - Min, Kyoungseon; Yeon, Young Joo; Um, Youngsoon; Kim, Yong Hwan (Elsevier BV, 2016)
Pyruvate is a significant platform chemical widely used in the agrochemical and pharmaceutical industries. We discovered FAD-containing lactate dehydrogenases (LDHs) from Acetobacter aceti (Aa-LDH) and Acidocella species MX-AZ02 (As-LDH), expressed them in Escherichia coil, optimized their FAD reconstitution, and characterized the recombinants as NAD-independent D-LDHs that are capable of the in vitro biocatalytic production of pyruvate from lactate. Instead of NAD, both Aa-LDH and As-LDH utilized various organic dyes as the electron acceptor. In addition, Aa-LDH and As-LDH exhibited substrate specificity for D-lactate only. Activity was optimized at pH 7.0 and 65 degrees C. The kinetic parameters of Aa-LDH and As-LDH were examined and both enzymes exhibited higher catalytic efficiency (k(cat)/K-m) for 2,6-dichlorophenolindophenol (DCIP), one of the electron acceptors, than D-lactate due to higher binding affinities. When using 10 mM D-lactate as the substrate with stepwise DCIP and D-LDH feeding, Aa-LDH and As-LDH produced 5.48 and 4.09 mM pyruvate, respectively, and the conversion was proportional to the DCIP concentration. (C) 2015 Elsevier B.V. All rights reserved.